Influence of adding iron-steel waste materials on hot metal quality - Vernilli, Fernando; Silva, Sidiney Nascimento; Longo, Elson [UNESP]; Saito, Eduardo; Nascimento, Vinicius Franco; Cangani, Maxwell Pereira (My University, 2008)
Hazardous waste materials, notably industrial ones, are of particular concern, inasmuch as if they are not dealt with adequately, they may pose a serious threat to the environment. In this connection, those industries which develop reuse and/or recycling policies for their wastes in their own manufacturing processes, next to addressing the environmental issue, will, to some degree, be replacing their waste generation by co-products. Further, the gain will be even more substantial if reuse is followed by a lower energy and/or feedstock consumption. This paper looks into the behavior of some waste materials from the iron-steel industry, such as BOF fine sludge, rolling scale and iron oxide stemming from the Acid Regeneration Plant (ARP), aimed at their recycling as treatment agents to pre-refine hot metal. Lab tests suggested that such waste materials from the iron-steel industry may be used as ancillary agents to pre-refine hot metal. However, since lab test results are not absolute, industrial trials are being conducted and the preliminary results are quite promising.
Keywords: Dephosphorization; Desulfurization; Wastes from the iron-steel industry